Locally managed irrigation systems: essential tasks and implications for assistance, management transfer and turnover programs - Yoder, R. (International Irrigation Management Institute, 1994)
This monograph examines the construction, operation and maintenance tasks that shape the nature of locally managed irrigation systems. The objective of the book is to identify relevant experiences and lessons for staff who are responsible for working with locally managed systems in three types of programs: direct assistance to existing locally managed irrigation systems, turnover of public owned systems to local management, and transfer of partial management to farmer groups within larger systems that remain publicly controlled.